GPR12 Inhibits Apoptosis in Epithelial Ovarian Cancer via the Activation of ERK1/2 Signaling - Wang, Lu; Yang, Da; Zhang, Yao; Jiao, Yisheng (Frontiers in Oncology, 2022)
Epithelial ovarian cancer (EOC) is one of the most lethal gynecological malignancies in women worldwide. G protein–coupled receptor 12 (GPR12) is a member of G protein–coupled receptors (GPCRs) and plays an important role in the regulation of cell proliferation and survival. However, its role in EOC is underappreciated. In this study, we found that GPR12 is highly expressed in the EOC tissues and can be an ideal biomarker to predict the prognosis of patients with EOC. GPR12 knockdown obviously inhibits the proliferation of EOC cells by inducing cellular apoptosis in vitro and in vivo. Meanwhile, bioinformatic analysis showed that the inhibitory effect of GPR12 knockdown on the cell viability is closely related with Extracellular signal-regulated kinases 1/2 (ERK1/2) pathway, which has been confirmed by the fact that the activity of ERK1/2 pathway has been significantly blocked in the GPR12 knockdown cells. LM22B-10, ERK1/2 pathway activator, could reverse the inhibited proliferation caused by GPR12 knockdown in the EOC cells. Our findings suggest that GPR12 is involved in the EOC process and is a potential therapeutic target for EOC.